Implementasi Strategi Guru Bimbingan Dan Konseling Dalam Mengatasi Perilaku Perundungan Pada Remaja Awal (12-15 tahun) - Sabit Tohari; Muhammad Eka Prasetia; Sri Ayatina Hayati (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2023)
Today’s young generation is not fully able to fulfil the aspects of the ideal character needed to sustain the progress and success of a nation in the future. Strawberry Generation represents strawberries that are beautiful but easily brittle and crumble when stepped on. The emergence of Strawberry Generation is influenced by several factors, one of which is parenting in educating and raising their children. Researchers are interested in studying more about the skills of parents in educating children today. The use of phenomenological methods as an effort to describe and reveal how the skills of parents in educating children today and how behavioural changes that occur as a result of parenting to the parable of the term often referred to as generation Z, namely strawberry generation. The results of this study found that the skills of parents in educating children who have the potential to grow them to be part of the strawberry generation, including overprotective parenting, authoritarian parenting, lack of appreciation and communication. Solutions to minimize children becoming Strawberry Generation include: 1) mental build; 2) give confidence to children to carry out responsibilities that can make them learn and upgrade themselves, so that children feel they contribute and feel valuable; 3) attachment between parents and children; 4) train children to make decisions; 5) always understand the the child’s condition; 6) instilling a growth mindset. Keywords: Counseling Teacher Strategy, Bullying behavior